2016
DOI: 10.17860/efd.94338
|View full text |Cite
|
Sign up to set email alerts
|

Using Writing Templates as Materials to Improve Writing Skills in Intermediate (B1) EFL Classes: An Experimental Study

Abstract: In this study it was aimed at revealing the findings of an experimental study in which writing templates were used as writing materials to improve writing skills in intermediate (B1) EFL classes as well as reviewing the concepts writing skills, second language writing and writing templates. The study was conducted with 50 students, aged 20-23, of a public university in Turkey. In Writing and Speaking in English II class writing templates were used as writing materials during 12 weeks. The students were asked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Also, it benefits in greater learning reten on and applica on in daily life. Likewise, a study was conducted by Akdemir and Eyerci (2016) and the main focus of this study was on applying wri ng templates as materials to develop wri ng skills in EFL classes. And the result demonstrated that choosing suitable materials had a frui ul factor on students wri ng skill.…”
Section: Methodsmentioning
confidence: 99%
“…Also, it benefits in greater learning reten on and applica on in daily life. Likewise, a study was conducted by Akdemir and Eyerci (2016) and the main focus of this study was on applying wri ng templates as materials to develop wri ng skills in EFL classes. And the result demonstrated that choosing suitable materials had a frui ul factor on students wri ng skill.…”
Section: Methodsmentioning
confidence: 99%
“…This includes grammar, vocabulary, sentence structure, punctuation, and spelling (Hayes, 1996;Kellogg, 1996;Alotaibi, 2019;. Such demands make writing a complex process and an overwhelming task, and foreign language (FL) writers are often faced with significant challenges in developing their writing skills (Akdemir & Eyerci, 2016;Evans, Hartshorn, McCollum, & Wolfersberger, 2010).…”
Section: Review Of Literaturementioning
confidence: 99%
“…It requires focusing on higher level skills of planning and organizing as well as lower level skills of spelling, punctuation and word choice (Alotaibi, 2019;Richards & Renandya, 2002). That's why writing is a complex process and a daunting task and second language (L2) writers usually face significant challenges in developing their writing skills (Akdemir & Eyerci, 2016;Evans, Hartshorn, McCollum, & Wolfersberger, 2010).…”
Section: Introductionmentioning
confidence: 99%